Age, growth, maturity and extinction risk of an exploited and endangered skate, Atlantoraja castelnaui, from off Uruguay and northern Argentina - Barbini, Santiago Aldo (2021)
The spotback skate Atlantoraja castelnaui (Arhynchobatidae) is a large and threatened skate species subjected to fishing pressure, endemic to the Southwest Atlantic that occurs from Rio de Janeiro, Brazil, to San Jorge Gulf, Argentina. The age, growth, age at maturity and the maximum intrinsic rate of population increase rmax of A. castelnaui were studied using 152 specimens collected from off Uruguay and north Argentina (35°–42° S), between June 2013 and February 2020. Vertebrae from 143 individuals were used for ageing (females: n = 83, size range 404–1300 mm total length, TL; males: n = 60, size range 400–1270 mm TL). Maximum ages determined for females and males were 30 and 28 years, respectively. To fit growth models, non-linear and Bayesian estimation approaches were considered. For the first approach, a set of four candidate growth (size-at-age) models were fitted: three-parameter von Bertalanffy, two-parameter von Bertalanffy with fixed L0, Gompertz and Logistic. In the second approach, von Bertalanffy, Gompertz and Logistic were fitted. For non-linear estimation, model selection indicated that the entire set of candidate growth models were supported by the data. The von Bertalanffy was selected as the best model for Bayesian estimation. There were no differences in growth between sexes. For the sexes combined, the von Bertalanffy growth model by Bayesian method was considered the most adequate to describe the growth of A. castelnaui (growth mean parameters ± S.D.: L∞ = 1210.29 ± 40.68 mm; k = 0.12 ± 0.01 years−1; L0 = 179.20 ± 11.62 mm). The age at maturity was estimated at 16.21 and 14.04 years for females and males, respectively. The maximum intrinsic rate of population increase rmax was estimated as 0.252 years−1. Life-history traits and rmax provided in the present study suggest that this species has a relatively low productivity and may be vulnerable to an intense fishing pressure.